A Comparison of Techniques for 90Y PET/CT Image-Based Dosimetry Following Radioembolization with Resin Microspheres - Pasciak, Alexander S.; Bourgeois, Austin C.; Bradley, Yong C. (Frontiers in Oncology, 2014)
90Y PET/CT following radioembolization has recently been established as a viable diagnostic tool, capable of producing images that are both quantitative and have superior image quality than alternative 90Y imaging modalities. Because radioembolization is assumed to be a permanent implant, it is possible to convert quantitative 90Y PET image sets into data representative of spatial committed absorbed-dose. Multiple authors have performed this transformation using dose-point kernel (DPK) convolution to account for the transport of the high-energy 90Y β- particles. This article explores a technique called the Local Deposition Method (LDM), an alternative to DPK convolution for 90Y image-based dosimetry. The LDM assumes that the kinetic energy from each 90Y β- particle is deposited locally, within the voxel where the decay occurred. Using the combined analysis of phantoms scanned using 90Y PET/CT and ideal mathematical phantoms, an accuracy comparison of DPK convolution and the LDM has been performed. Based on the presented analysis, DPK convolution provides no detectible accuracy benefit over the LDM for 90Y PET-based dosimetry. For PET systems with 90Y resolution poorer than 3.25 mm at full-width and half-max using a small voxel size, the LDM may produce a dosimetric solution that is more accurate than DPK convolution under ideal conditions; however, image noise can obscure some of the perceived benefit. As voxel size increases and resolution decreases, differences between the LDM and DPK convolution are reduced. The LDM method of post-radioembolization dosimetry has the advantage of not requiring additional post-processing. The provided conversion factors can be used to determine committed absorbed-dose using conventional PET image analysis tools. The LDM is a recommended option for routine post-radioembolization 90Y dosimetry based on PET/CT imaging.